Malignant Renal Angiomyolipoma With Metastases in a Child. (April 2014) - Xi, Shaoyan; Chen, Huadong; Wu, Xingping; Jiang, Hong; Liu, Juncheng; Wu, Qiuliang; Zeng, Jing
The biological character of epithelioid angiomyolipoma (EAML) remains controversial and little is known about EAML in children. We present a case of a 7-year-old boy with abdominal distention, diagnosed as EAML. Under microscopy, epithelioid cells were observed, with eosinophilic or slightly eosinophilic cytoplasm and nuclear pleomorphism, thick-walled blood vessels, and some cells that were differentiated to smooth muscle cells or fat cells were easily observed. Immunochemical staining showed that Melan-A and HMB45 were positive. The tumor presented highly aggressive biobehavior. Furthermore, we reviewed and analyzed cases of diagnosed EAML in our hospital and those reported in the literature. Renal EAML (10/17) was most common, and the EAML of 3 of 17 patients metastasized to other organs.